2015
DOI: 10.1007/s10753-015-0131-3
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib Combined with Diacerein Effectively Alleviates Osteoarthritis in Rats via Regulating JNK and p38MAPK Signaling Pathways

Abstract: Osteoarthritis (OA) has long been a difficult to overcome joint disease for medical workers. However, there is still a lack of effective treatments for OA. In the present study, we aimed to evaluate the treatment effect of celecoxib (CLX) combined with diacerein (DC) on OA and delineate the underlying molecular mechanism. The OA model was established by using rats, and OA rats were treated with either CLX alone, DC alone, and CLX combined with DC. The results showed that, as compared with a single treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
0
21
0
3
Order By: Relevance
“…In endothelial cells, the JNK signaling pathway specifically mediates the expression of cyclooxygenase-2 (Cox-2) and matrix metalloproteinase-13 (MMP-13) in response to a variety of cytokines (34,35). As revealed by RT-PCR, Cox-2 and MMP-13 transcription was significantly increased in HUVECs following treatment with 20 µM DHA for 24 h (P=0.010 and P=0.020, respectively; Fig.…”
Section: Dha Induces the Expression Of The Downstream Genes Of The Jnmentioning
confidence: 93%
“…In endothelial cells, the JNK signaling pathway specifically mediates the expression of cyclooxygenase-2 (Cox-2) and matrix metalloproteinase-13 (MMP-13) in response to a variety of cytokines (34,35). As revealed by RT-PCR, Cox-2 and MMP-13 transcription was significantly increased in HUVECs following treatment with 20 µM DHA for 24 h (P=0.010 and P=0.020, respectively; Fig.…”
Section: Dha Induces the Expression Of The Downstream Genes Of The Jnmentioning
confidence: 93%
“…NO can induce cartilage matrix degradation by suppressing proteoglycan synthesis, activating MMPs, and inducing cartilage degradation 31 . Zweers et al showed that celecoxib inhibited NO depending on the chondrocyte cell culture model 6 , and some studies did not confirm NO suppression by celecoxib 19e21, 32 . A rat arthritis model reviewed showed better OA attenuation with celecoxib and anthraquinone diacerein combination than either drug alone.…”
Section: Effects On Cytokines/mmpmentioning
confidence: 99%
“…As a result of the poor self-repair ability of cartilage, preventing COL2 degradation in cartilage injury is the key factor in inhibiting further cartilage degeneration and OA progression (12). Interleukin (IL)-1β is the most important proinflammatory cytokine in the pathophysiology of OA, which serves a key role in COL2 degradation (13,14). It has been reported that IL-1β could upregulate the Wnt5a protein, and the Wnt5a protein could activate the Jun amino-terminal kinase (JNK) signaling pathway, inducing the upregulation of matrix metalloproteinases (MMPs) (15,16).…”
Section: Introductionmentioning
confidence: 99%